Crises através dos tempos: um discurso crítico de Ernesto Sábato - Fatio, Carla (Universidade de São Paulo | Escola de Comunicações e Artes, 2020)
This paper analyzes how the relevance of art criticism under the perspective of Ernesto Sabato after submitting his contribution to the Symposium of the First Latin American Biennial of 1978. We describe his world view when comparing life based on the worship of technique and that based on the exploration caused by man. We verify the ethical-moral variations and the significance of his critical thinking focused on the psychosomatic process of humans and their endless search and transcendence in the face of socio-political and moral crises. We evaluated his critical discourse, the mythical processes evidenced in his dialectical reflections on art, and the identity of the various philosophical movements described.